Stem borer insects on Hopea odorata in Bogor, West Java, Indonesia: Stem Borer Insects on Merawan - NOOR FARIKHAH HANEDA; Mulia Furqon; Muhammad Suheri (Society for Indonesian Biodiversity, 2020)
Abstract. Haneda NF, Furqan M, Suheri M. 2020. Stem borer insects on Hopea odorata in Bogor, West Java, Indonesia. Biodiversitas 21: 5308-5316. Hopea odorata Roxb. locally known as “merawan”, is a dipterocarp species that has the potentials to be developed for plantation forestry. Nonetheless, anecdotal evidence in Bogor, West Java, Indonesia, suggested that the trees suffered serious attacks caused by stem borer insects, causing defoliation of the crown and leading to stunted growth and death. This phenomenon suggests a more systematic investigation. The objectives of this research were: (i) to identify the species of stem borer which attacked H. odorata; (ii) to investigate the types and forms of the damage of H. odorata tree due to stem borer attack; and (iii) to study the effects of stem borer attack on the tree and wood of H. odorata. The results showed that all species of stem borer insects belong to Coleoptera, namely as Xyleborus perforans (Scolytidae), Xyleborinus perexiguus (Scolytidae), Platypus parallelus (Platypodidae), Belionota prasina (Buprestidae), Curculionid beetle, and Tenebrionid beetle. The number of boring holes on a single tree was 1932 holes, of which 98.6% caused by ambrosia beetles: Xyleborus perforans (1426 holes, 73.8%), Xyleborinus perexiguus (457 holes, 23.7%), and Platypus parallelus (21 holes, 1.1%). The length of boring tunnel at cross-section ranged between 2-35 cm and at longitudinal section ranged between 4-6 cm. The number of boring holes decreased along with the increasing height of tree stem. The patterns of boring tunnel at stem cross-section were branching (X. perforans, P. parallelus); encircled (X. perforans), black stains along their wall (X. perexiguus, X. perforans, P. parallelus).